KEEFEKTIFAN KITOSAN DALAM MENGENDALIKAN Botryodiplodia theobromae Pat. PENYEBAB MATI PUCUK PADA BIBIT JABON (Anthocephalus cadamba (Roxb.) Miq) Chitosan’s Effectiveness in Controlling Dieback by Botryodiplodia theobromae Pat on Jabon Seeding - Desi Nurafida; Achmad .; Syamsul Falah (Jurnal Silvikultur Tropika, 2017)
Dieback disease by the fungus Botryodiplodia theobromae in Jabon seedlings (Anthocephalus cadamba) inhibits the regeneration of Jabon plant. Synthetic fungicides utilization to several problems such as residue on the environment and pathogen resistance. Chitosan is a potential natural compound used as an alternative to control plant disease.This research aims to examine the effectiveness of chitosan to control B. theobromae as causal agent of dieback on Jabon seedlings and to examine the effect of chitosan to control the viscosity of dieback disease on Jabon seedlings. The results showed that the chitosan solution can decrease the severity of disease in Jabon seedlings. However, it was different with the disease incidence rate parameter. Chitosan solution was not significantly affecting the disease because B. theobromae caused dieback symptoms on Jabon seedlings. The most effective treatment was chitosan solution with a concentration of 0.1% before inoculation with the severity of the disease by 25%. Chitosan solution viscosity was responsible in affecting the percentage of dieback disease in Jabon seeds. The higher the viscosity of chitosan, the higher the percentage of dieback disease attacks. The best viscosity to suppress the development of dieback disease on Jabon seedlings was 8.80 with 7.90% attack.Key words: Anthocephalus cadamba , Botryodiplodia theobromae, chitosan, dieback.